Type 2 diabetes in older patients: an analysis of the DPV and DIVE databases. (September 2020) - van Mark, Gesine; Tittel, Sascha R.; Sziegoleit, Stefan; Putz, Franz Josef; Durmaz, Mesut; Bortscheller, Michaela; Buschmann, Ivo; Seufert, Jochen; Holl, Reinhard W.; Bramlage, Peter
Background: The clinical profile differs between old and young patients with type 2 diabetes mellitus (T2DM). We explored, based on a large real-world database, patient and disease characteristics and actual treatment patterns by age. Methods: The analysis was based on the DIVE and DPV registries of patients with T2DM. Patients were analyzed by age groups 50–59 (middle-young), 60–69 (young-old), 70–79 (middle-old), 80–89 (old), and 90 years or more (oldest-old). Results: A total of 396, 719 patients were analyzed, of which 17.7% were 50–59 years, 27.7% 60–69 years, 34.3% 70–79 years, 18.3% 80–89 years and 2.0% at least 90 years. We found that (a) T2DM in old and oldest-old patients was characterized much less by the presence of metabolic risk factors such as hypertension, obesity, dyslipidemia and smoking than in younger patients; (b) the HbA1c was much lower in oldest-old than in middle-young patients (7.2 ± 1.6% versus 8.0 ± 2.2%; p  < 0.001), but it was associated with higher proportions of patients with severe hypoglycemia (7.0 versus 1.6%; p  < 0.001); (c) this was potentially associated with the higher and increasing rates of insulin use in older patients (from 17.6% to 37.6%, p  < 0.001) and the particular comorbidity profile of these patients, for example, chronic kidney disease (CKD); (d) patients with late diabetes onset had lower HbA1c values, lower bodyweight and less cardiovascular risk factors; (e) patients with a longer diabetes duration had a considerable increase in macrovascular and even more microvascular complications. Conclusion: In very old patients there is a need for frequent careful routine assessment and a tailored pharmacotherapy in which patient safety is much more important than blood-glucose-lowering efficacy.